Letting in-vehicle navigation lead the way: Older drivers' perceptions of and ability to follow a GPS navigation system. (September 2017) - Stinchcombe, Arne; Gagnon, Sylvain; Kateb, Matthew; Curtis, Meredith; Porter, Michelle M.; Polgar, Jan; Bédard, Michel
Abstract: In-vehicle navigation systems have the potential to simplify the driving task by reducing the drivers' need to engage in wayfinding, especially in unfamiliar environments. This study sought to characterize older drivers' overall assessment of using in-vehicle GPS technology as part of a research study and to explore whether the use of this technology has an impact on participants' driving behaviour. Forty-seven older drivers completed an on-road evaluation where directions were provided by an in-vehicle GPS navigation system and their behaviour was recorded using video technology. They later completed a questionnaire to assess their perception of the navigation system. After the study, participants were grouped based on whether they were able to accurately follow the instructions provided by the navigation system. The results indicated that most drivers were satisfied with the navigation technology and found the directions it provided to be clear. There were no statistically significant differences in the number of on-road errors committed by drivers who did not follow the directions from the navigation system in comparison to drivers who did follow the directions.